2020
DOI: 10.1016/j.engstruct.2019.109810
|View full text |Cite
|
Sign up to set email alerts
|

Design recommendations for stainless steel I-sections under concentrated transverse loading

Abstract: Recent investigations have highlighted the need for improved provisions for determining the resistance of stainless steel I-sections under concentrated transverse loading. Such provisions, which reflect the particular characteristics of the material, have been developed and are described herein. A review of the existing European design formulae for members under concentrated transverse loading is firstly presented. Then a series of parametric studies, based on validated finite element models are described cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Table 3 shows the results for these calibrations. It is worth pointing out that for the effective load length š‘™ š‘¦ -in Equation ( 8)-in the calibration conducted by Graciano et al [16] the best results were attained with š‘š 2 ā‰  0, and dos Santos and Gardner [17] only considered š‘š 2 =0.…”
Section: Calibration Of the Resistance Function š›˜ š…mentioning
confidence: 98%
See 3 more Smart Citations
“…Table 3 shows the results for these calibrations. It is worth pointing out that for the effective load length š‘™ š‘¦ -in Equation ( 8)-in the calibration conducted by Graciano et al [16] the best results were attained with š‘š 2 ā‰  0, and dos Santos and Gardner [17] only considered š‘š 2 =0.…”
Section: Calibration Of the Resistance Function š›˜ š…mentioning
confidence: 98%
“…Employing a standard evaluation procedure provided in EN 1990 [24], Graciano et al [16] and dos Santos and Gardner [17] calibrated, the imperfection factor š›¼ š¹0 and the plateau length šœ† Ģ… š¹0 for a given level of safety š›¾ š‘€1 . Table 3 shows the results for these calibrations.…”
Section: Calibration Of the Resistance Function š›˜ š…mentioning
confidence: 99%
See 2 more Smart Citations
“…web thickness tw and web yield stress fyw. By considering the variability of each independent variable, as well as accounting for variability generated by the use of numerical data and the amount of data used, it was found that the proposed design equations presented in Section 4.3, with coefficients presented in Table 3, can be safely applied to the design of stainless steel members under concentrated transverse loading with a partial factor Ī³M1 equal to 1.1 [15]. Introduction elastic buckling load, from which the element slenderness and hence the element resistance can be determined.…”
Section: Reliability Analysismentioning
confidence: 99%